Nutrient Management in Summer Sesame (Sesamum indicum L.) and its Residual Effect on Black Gram (Vigna mungo L.) - Ghosh, A. K.; Duary, B.; Ghosh, D. C. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were carried out to study the effect of nutrient management in summer sesame and its residual effect on succeeding kharif black gram during 2003 and 2004 in sub-humid lateritic tract of West Bengal. The crop growth was better with integrated application of 50% recommended dose of NPK through fertilizer (RDF), 50% N through vermicompost (VC) or FYM along with Azospirillum in sesame. The number of capsules plant-1, seeds capsule-1, seed and oil yield of sesame increased significantly due to integrated application of 50% RDF+50% N through FYM along with Azospirillum in sesame during both the years. However, the treatment was at par with those of 75% RDF+25% N through FYM or VC along with Azospirillum and 50% RDF+50% N through VC along with Azospirillum. Integrated use of fertilizer, organic manure and Azospirillum produced higher seed and oil yield of sesame compared to 100% RDF through fertilizer alone. Further, substitution of 25% N through FYM along with Azospirillum produced higher seed and oil yield of sesame than that of 100% RDF. Integrated use of 50% RDF+50% N through FYM+Azospirillum recorded 12.2, 20 and 15.6% higher yield over 100% RDF in 2003, 2004 and pooled over the years, respectively. This treatment also gave higher gross and net return. Application of 50% RDF and 50% N through vermicompost or FYM along with Azospirillum in sesame exerted greater residual effect on the growth, yield components and seed yield of succeeding black gram as compared to other treatments. It also helped in improving the fertility status of the soil under this cropping system in red and lateritic belt of West Bengal.